Membuktikan Anggapan Analisa Geoteknik (Tekanan Sisi Tanah) Menggunakan Model Fizikal - Beddu, Salmia (Universiti Sains Malaysia, 2006)
The purpose of this research is to verify certain geotechnical assumptions for associated with lateral earth pressures using physical modeling. The model used of this study is made of wood and Perspex. The static test with loading on top of sand decrease with depth which is in contradiction with the theory. This result however can be explained by considering the stress bulb theory where pressure due to loading generally reduces with depth. After some improvement, the pressure distribution for sand without extra loading on top show a result of lateral earth pressure which increase with depth. Furthermore, by adding a load on top of the sand, a superimposed effect was observed which is the stress bulb distribution plus the normal static lateral pressure distribution. A dough of wheat flour was also used as the material and the result shows a pressure distribution increase with depth and partially verifies the passive Rankine pressure. Test involving laterite material were too difficult to conduct.